One-Step Detection of Explosives Using a Self-Developed Computer Program Based on Application of a Principal Component Analysis in Prompt g-Spectra - Im, Hee-Jung; Lee, Yun-Hee; Chul Song, Byoung; Joon Park, Yong (Asian Journal of Chemistry, 2014)
A one-step process for the detection of an explosive was developed from tests and experimental data, and the achieved detection was based on the samples’ relative elemental composition ratios. According to a self-developed computer program, collected g-spectra by prompt g-ray neutron activation analysis were applied to a principal component analysis to increase the signal-to-noise ratio and to discriminate the explosives from non-explosive materials. A test sample was successfully run through the program and could be detected as an explosive or a non-explosive with a reasonable error rate.